Elevation of transaminases. What if not the liver? - I. V. Sharkova (Лечащий Врач)
Background. According to Russian studies, the average age of Duchenne muscular dystrophy diagnosis is 7-8 years. This is because, on one hand, Duchenne muscular dystrophy is a rare disease, and a doctor may never see it throughout their clinical practice. On the other hand, the clinical picture of the disease is diverse and does not have pronounced symptoms in the early stages of development. Doctors often make mistakes in diagnosis by considering the consequences of the disease or focusing on one manifestation without seeing the entire complex of symptoms and its root cause. For example, one of the manifestations of the disease is elevated liver enzymes: transaminases (ALT, AST) and LDH. About 50% of misdiagnoses in Duchenne muscular dystrophy are related to liver damage. These children may be observed for years by infectious disease specialists or pediatric gastroenterologists with unspecified diagnoses, undergoing new and sometimes invasive tests.Conclusion. Currently, many patients with Duchenne muscular dystrophy have access to pathogenetic therapy. Unfortunately, it does not restore lost functions but can preserve existing ones and clinically convert the aggressive form of Duchenne muscular dystrophy into a milder Becker form. This is why it is crucial to inform primary care pediatricians, pediatric gastroenterologists, and infectious disease specialists about the mechanisms of non-hepatic transaminase elevation and diagnostic algorithms for muscular dystrophies.